Conceptualising cultural safety at an Indigenous-focused midwifery practice in Toronto, Canada: qualitative interviews with Indigenous and non-Indigenous clients - Michelle Firestone; Sara H Wolfe; Cheryllee Bourgeois; Janet K Smylie; Mackenzie E Churchill; Helle Moeller (BMJ Open)
Objective Cultural safety is an Indigenous concept that can improve how healthcare services are delivered to both Indigenous and non-Indigenous peoples in Canada. This study explored how Indigenous and non-Indigenous clients at an urban, Indigenous-focused midwifery practice in Toronto, Canada (Seventh Generation Midwives Toronto, SGMT) conceptualised and experienced culturally safe care.Design and setting Interviews were conducted with former clients of SGMT as a part of a larger evaluation of the practice. Participants were purposefully recruited. Interviews were transcribed and analysed thematically using an iterative, consensus-based approach and a critical, naturalistic, and decolonising lens.Participants Saturation was reached after 20 interviews (n=9 Indigenous participants, n=11 non-Indigenous participants).Results Three domains of cultural safety emerged. Each domain included several themes: Relationships and Communication (respect and support for choices; personalised and continuous relationships with midwives; and being different from past experiences); Sharing Knowledge and Practice (feeling informed about the basics of pregnancy, birth, and the postpartum period; and having access to Indigenous knowledge and protocols), and Culturally Safe Spaces (feeling at home in practice; and having relationships interconnected with the physical space). While some ideas were shared across groups, the distinctions between the Indigenous and non-Indigenous participants were prominent.Conclusion The Indigenous participants conceptualised cultural safety in ways that highlight the survival and resurgence of Indigenous values, understandings, and approaches in cities like Toronto, and affirm the need for Indigenous midwives. The non-Indigenous participants conceptualised cultural safety with both congruence, illuminating Black-Indigenous community solidarities in cultural safety, and divergence, demonstrating the potential of Indigenous spaces and Indigenous-focused midwifery care to also benefit midwifery clients of white European descent. We hope that the positive impacts documented here motivate evaluators and healthcare providers to work towards a future where ‘cultural safety’ becomes a standard of care.